Prediction of the mechanical behavior of fiber-reinforced composite structure considering its shear angle distribution generated during thermo-compression molding process. (15th July 2019) - Kim, Dug-Joong; Yu, Myeong-Hyeon; Lim, Jaeyoung; Nam, Byeunggun; Kim, Hak-Sung
Abstract: In this study, a combined forming-structural analysis of composite structures was performed. Fiber orientation and shear angle changes of the composite materials during its thermo-compression molding processes were predicted with commercial software PAM-FORM. In addition, the material properties, such as elastic modulus and strength, from the shearing of woven fabrics, were measured. The predicted shear angle changes were transformed and reflected to the structural analysis by a self-developed vector-mapping program. The load-displacement curves of the composite structures from the combined forming and structural simulation were compared with the experimental compression and bending test results of hemispherical and U-shaped components, respectively. Finally, it was found that the mechanical behaviors of composite structures can be accurately predicted by the developed combined thermo-forming structural analysis method.